Multiple Pricing for Personal Assistance Services - Tommy Andersson; Lina Maria Ellegård; Andreea Enache; Albin Erlanson; Prakriti Thami (Lund University, School of Economics and Management, Department of Economics, 2022)
This paper provides a general theoretical framework that captures the essential features of a Swedish reform where private and public health care providers serve patients with certain functional impairments. Because providers receive a fixed hourly compensation for their services (identical across patient types) and only private providers can reject service requests from patients, private providers avoid the costliest patients, resulting in a monetary deficit for public providers. To partially overcome this problem, a multiple pricing (reimbursement) scheme is proposed and its solution is characterized. The results suggest that there are some fundamental trade-offs, e.g., between the goals of containing costs and restricting choices for patients, but that the suggested pricing scheme may substantially reduce the deficits for public providers without affecting the total budget set by the central government.
Keywords: C61; D47; D78; I11; 330; health care services; public and private providers; multiple pricing; welfare; dumping